Violência doméstica contra a mulher : prevenção, repressão e políticas públicas no Brasil - Cavalcanti, Stela Valéria Soares de Farias (2006)
This research work deals with the system for the prevention and repression of domestic violence against women in Brazil, considered one of the most serious human rights violations. The principles of equality, public policies and affirmative actions for the promotion of isonomic laws for the different genders are also discussed. In the present study, domestic violence, apart from being a crime, is also treated as one of the most insidious forms of discrimination, intolerance and disrespect for human dignity. In addition, the study makes the distinction between domestic and non-domestic violence, in order to prevent them from receiving the same treatment. Further, the main causes and consequences of this kind of crime, as well as the profile of the victims and aggressors, are analyzed based on statistical data on domestic violence against women in Brazil and in other countries. Women rights are presented as part of the human rights, according to the most important treaties published by the United Nations and by the Organization of American States. The study includes the analysis of the models for the prevention of domestic violence used in European and Latin American countries. Also included are the penal legislation and the public policies developed in Brazil after the 1988 Constitution to implement the principle of equality (see art. 5º, I). In this sense, the limitations of the Law nº 9.099/95 and the sanctions included in the Brazilian Penal Code to repress this kind of offense are discussed. Finally, the study presents proposals in order to promote equality between men and women in both social and family relations, with a view to prevent and punish the domestic violence in Brazil, through legislative changes and effective public actions.